Prevalence and factors associated with smoking intentions among non-smoking and smoking adolescents in Kota Tinggi, Johor, Malaysia - Lim, Kuang Hock; Mohamad Ghazali, Sumarni; Kee, Chee Cheong; Lim, Kuang Kuay; Lim, Hui Li; Teh, Chien Huey; Chan, Ying Ying; Yeo, Lay Yen; Goh, Fiona Swee Ching; Khoo, Yi Yi; Chong, Zhuo Lin; Ibrahim, Normala; et al. (Asian Pacific Education Press Ltd., 2014)
Intention to smoke is a valid and reliable factor for predicting future smoking habits among adolescents. This factor, however, has received inadequate attention in Malaysia. The present paper elaborates the prevalence and factors associated with intent to initiate or to cease smoking, among adolescent nonsmokers and smokers in Kota Tinggi, Johor, Malaysia. A total of 2,300 secondary school students aged 13-16 years were selected through a two-stage stratified sampling method. A set of standardized questionnaires was used to assess the smoking behavior among adolescents and the inter-personal and intra-personal factors associated with smoking intention (intention to initiate smoking or to cease smoking). Multivariable logistic regression was used to identify factors related to smoking intention. The prevalence of intention to smoke in the future or to cease smoking among nonsmoking adolescents and current smokers were 10.7% and 61.7% respectively. Having friends who smoke, social influence, and poor knowledge about the ill effects on health due to smoking showed significant relationships with intention to smoke in the future among non-smokers. Conversely, perceived lower prevalence of smoking among peers, weak contributory social influence, and greater awareness of the ill effects of smoking are factors associated with the intention to cease smoking sometime in the future. The study found that prevalence of intention to initiate smoking is low among non-smokers while the majority of current smokers intended to cease smoking in the future. Existing anti-smoking programmes that integrate the factors that have been identified in the current study should be put in motion to reduce the prevalence of intention to initiate smoking and increase the intention to cease smoking among adolescents.